ANALYSIS OF APPLICATION METHODS OF THE TONALITY AMENDMENT DURING GAS-TURBINE ENGINES DEVELOPMENT TESTS FOR CORRESPONDENCE WITH NOISE ENVIRONMENTAL REQUIREMENTS - Владимир Николаевич Журавлёв; Татьяна Владимировна Критская (Авіаційно-космічна техніка та технологія, 2018)
The important and actual task of the modern engine engineering is an objective estimation of gas-turbine engine noise levels during its development tests, which will allows to estimate the expected noise levels as part of aircraft. The problem is under review, whose content consists in the analysis of application methods of the tonality amendment during gas-turbine development tests for correspondence with environmental requirements.